The identity of Arhodia egenaria Walker, 1866 (Lepidoptera, Mimallonoidea, Mimallonidae) and a new synonym of Cicinnus melsheimeri (Harris, 1841) - Laurent, Ryan A. St; Mccabe, Timothy L. (Zootaxa, 2017)
The holotypes of Arhodia egenaria Walker, 1866 and Cicinnus primolus Schaus, 1928, syn. n., were examined. Both names are junior synonyms of C. melsheimeri (Harris, 1841). Cicinnus melsheimeri (as Perophora egenaria), sensu Hampson, 1904, is a misidentification of C. bahamensis St Laurent & McCabe, 2016.